Factors and characteristics of physical violence among healthcare workers of a tertiary hospital in Enugu, Nigeria - Onyia, Sussan U. Arinze; Chinawa, Awoere T.; Ndu, Anne C.; Okwor, Tochi J.; Agwu-Umahi, Olanike I.; Obionu, Ifeoma; Kassy, Wilson C.; Aguwa, Emmanuel N.; Okeke, Theodora A. (International Journal Of Community Medicine And Public Health, 2019)
Background: Healthcare workers (HCWs) especially those involved in patients’ care are at high risk of violence. The study is aimed at determining factors and characteristics of physical violence among HCWs in a tertiary hospital in Nigeria. Methods: The descriptive cross-sectional study was carried out among 412 HCWs from March to July, 2018. Data entry and analysis were done using Epi InfoTM 3.5.4 and Chi square and Fischer’s exact test where applicable were used to ascertain factors associated with physical workplace violence. Results: Respondents included 111 (26.9%) doctors and 301 (73.1%) nurses. Prevalence of physical violence was 12.6%. Of those who experienced workplace violence, the perpetrators were mainly patients’ relatives 37 (71.2%) and patients 8 (15.4%). In majority of cases, 28 (53.8%), no action was taken against the assailant. Prevalence of physical violence was significantly higher among nurses (15.3%) than doctors (5.4%) p=0.007. It is also higher among females (14.2%) than males (7.8%), although not significantly. Furthermore, HCWs who work in newborn units were most likely to experience physical violence. Conclusions: The study revealed that physical violence is prevalent among HCWs and violence prevention programs should be instituted to address it.